2018
DOI: 10.1176/appi.ps.201700298
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness in Regular Practice of Collaborative Care for Depression Among Adolescents: A Retrospective Cohort Study

Abstract: Collaborative care for adolescents in regular practice led to better remission and treatment response than usual care. Future studies could examine which groups might benefit most and flexible payment models to support these services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 23 publications
(16 reference statements)
0
40
0
Order By: Relevance
“…Thirteen studies included an integrated child psychiatrist or psychiatry trainee, who were most often part of a team with other integrated mental health providers (Briggs et al, 2016;Goodfriend et al, 2006;Levy et al, 2017;Horwitz et al, 2016;Moore et al, 2018;Rousseau et al, 2017;Schlesinger et al, 2017;Schlesinger, 2017;Subotsky & Brown, 1990;Talmi et al, 2016;German et al, 2017;Richardson et al, 2009;Shippee et al, 2018;Aguirre et al, 2013). Six studies evaluated an intervention delivered by members of the medical team (RNs, NPs, or midwives) with no prior mental health training (Kolko et al, 2010;Kolko et al, 2012;Kozlowski et al, 2015;Westerlund et al, 2017;Richardson et al, 2009;Shippee et al, 2018). No studies reported on the implementation of an integrated pediatric behavioral health intervention delivered exclusively by community health workers or other bachelor'slevel health care workers in primary care, and only one paper mentioned a parent partner (degree unspecified) who was included in care delivery in partnership with an LICSW (Yogman et al, 2018).…”
Section: Summary Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirteen studies included an integrated child psychiatrist or psychiatry trainee, who were most often part of a team with other integrated mental health providers (Briggs et al, 2016;Goodfriend et al, 2006;Levy et al, 2017;Horwitz et al, 2016;Moore et al, 2018;Rousseau et al, 2017;Schlesinger et al, 2017;Schlesinger, 2017;Subotsky & Brown, 1990;Talmi et al, 2016;German et al, 2017;Richardson et al, 2009;Shippee et al, 2018;Aguirre et al, 2013). Six studies evaluated an intervention delivered by members of the medical team (RNs, NPs, or midwives) with no prior mental health training (Kolko et al, 2010;Kolko et al, 2012;Kozlowski et al, 2015;Westerlund et al, 2017;Richardson et al, 2009;Shippee et al, 2018). No studies reported on the implementation of an integrated pediatric behavioral health intervention delivered exclusively by community health workers or other bachelor'slevel health care workers in primary care, and only one paper mentioned a parent partner (degree unspecified) who was included in care delivery in partnership with an LICSW (Yogman et al, 2018).…”
Section: Summary Of Included Studiesmentioning
confidence: 99%
“…While many studies reported interventions for children of all age ranges, others reported on interventions specific for certain age ranges, including early childhood, grade school-age children, and adolescents. Only three of the observational studies were disorder-specific, with two focused on ADHD (Moore et al, 2018;Olufs et al, 2016) and one (Shippee et al, 2018) on depression. Other observational studies were inclusive of all children within the target population (which at times was age-restricted) identified as needing mental health support.…”
Section: Summary Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, the efficacy and effectiveness of CoCM have been shown in more than eighty RCTs 1,2 . Additionally, using its core principles, others have extended CoCM to the treatment of individuals: (1) in a variety of treatment settings (e.g., inpatient treatment 3 and specialty medical care 4 ), (2) with a number of mental health diagnoses (e.g., anxiety 1 , bipolar disorder 5 and post-traumatic stress disorder 68 ) and (3) of different age ranges (e.g., adolescents 9 ). Despite its robust evidence base and extensive use, payment for this care model has remained a challenging task for states, municipalities, payers and healthcare systems.…”
Section: Introductionmentioning
confidence: 99%